Determinants of Consumer Behavior and Prospective Purchase Decisions in E-Commerce Environment: Evidence from Palestine - Al-Silwadi, Abdelrahman Hasan (Journal of Economic, Administrative and Legal Sciences, 2022)
This paper intends to study consumers’ behavior and attitudes towards e-business industry in the Palestinian territories, and investigates the most important factors influencing the adoption decision, and models E-consumer behavior process toward the mass customization in e-business industry depending in the theory of reasoned action and theory of planned behavior. The sole objective of the following paper, which has been conducted on the year 2022, is to give an in-depth overview of all literature associated with E-consumer behavior focusing on consumer behavior process toward e-business industry in the Palestinian territories. The focus then turns to investigate the theoretical and conceptual framework of consumer behavior, and identify all concepts, principles and theories that will serve as foundations for the later studies. A comprehensive literature review of consumer behavior and factors influencing the adoption decision of e-business organizations from the point view of individual customers are also presented. This paper is divided into six major parts. The first and second parts outlines the environmental influences and interpersonal and intrapersonal determinants of E-consumer behavior, which includes investigating the role of culture, social classes, social and reference groups, personality, attitudes and the role of learning in shaping E-consumer behavior toward adoption. The third and fourth sections outlines the theory of reasoned action and theory planned behavior that will serve as foundations for this study. The fifth section provides a comprehensive literature review of consumer behavior and factors influencing the adoption decision of e-business organizations in Palestine. Finally, Structured Equation Model (SEM) technique has been utilized and the LISREL 8 program was used to test the impacts of Attitudes towards using technology (ATT), Reference Groups (RG), Personality (P) and Cultural Impacts (CI) on Perceived Usefulness (PU), Perceived Confidence (PC) and Behavioral Intention (BI).